PENGUKURAN KESENJANGAN KINERJA ANTARA SUPPLIER DENGAN CUSTOMER PADA RANTAI PASOKAN JASA PENDIDIKAN TINGGI MENGGUNAKAN METODE SERVQUAL - Hagai Nicholas Ginting; Agung Sutrisno; Jefferson Mende (JURNAL POROS TEKNIK MESIN UNSRAT, 2017)
Performance is the key to measure the quality of service. On the other side an increase in the quality of service is one of the keys to winning the competition.The purpose of this study is measuring the service quality of services at the college using SERVQUAL. SERVQUAL method itself is a method to measure services through five dimensions namely Tangibels, Empathy, Reliability, Responsiveness and Assurance.The results of using SERVQUAL method from 25 variables obtained dimensions that has the biggest gap is Tangibels, Empathy, and Responsiveness.Â Keywords: Performance, SERVQUAL, Quality Gap